2005
DOI: 10.1093/jnen/64.2.147
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Multiple Sclerosis Is Location-Dependent: No Significant Complement Activation Is Detected in Purely Cortical Lesions

Abstract: Complement activation is known to occur in white matter multiple sclerosis (MS) lesions. It is thought to mediate oligodendrocyte/myelin damage and to be a marker of pathologic heterogeneity among individuals. Less is known about complement deposition in the gray matter in MS. The aim of this study was to characterize the presence and distribution of complement activation products in cortical MS lesions. Immunohistochemical staining was performed on cryostat sections from the brains of 22 MS patients and 5 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 35 publications
5
111
0
5
Order By: Relevance
“…8 Within rare active lesions, the intensity of the macrophage infiltrate mirrors myelin density and therefore varies according to location within the thalamus. Similar to changes demonstrated in cortical GM lesions of autopsy cases, [22][23][24] both adaptive (T and B cell perivascular and parenchymal infiltration) and innate (microglial activation/macrophage infiltration) inflammation in the thalamus is constrained when compared with classic active WM lesions, 8 a factor that potentially limits neuroaxonal injury in evolving lesions. However, this view has been recently challenged by Lucchinetti et al, 3 who demonstrate significant cortical GM inflammation in biopsy cases of early MS. Sampling bias in both early biopsy and end-stage autopsy studies may explain these discrepant findings; larger neuropathologic studies of the subcortical GM structures are required in order to corroborate or refute these observations.…”
Section: Zivadinov Et Al (2012) 44 233 Ms (169 Rrms and 4 Spms) And mentioning
confidence: 77%
“…8 Within rare active lesions, the intensity of the macrophage infiltrate mirrors myelin density and therefore varies according to location within the thalamus. Similar to changes demonstrated in cortical GM lesions of autopsy cases, [22][23][24] both adaptive (T and B cell perivascular and parenchymal infiltration) and innate (microglial activation/macrophage infiltration) inflammation in the thalamus is constrained when compared with classic active WM lesions, 8 a factor that potentially limits neuroaxonal injury in evolving lesions. However, this view has been recently challenged by Lucchinetti et al, 3 who demonstrate significant cortical GM inflammation in biopsy cases of early MS. Sampling bias in both early biopsy and end-stage autopsy studies may explain these discrepant findings; larger neuropathologic studies of the subcortical GM structures are required in order to corroborate or refute these observations.…”
Section: Zivadinov Et Al (2012) 44 233 Ms (169 Rrms and 4 Spms) And mentioning
confidence: 77%
“…Accurate classification of purely intracortical lesions is the first step toward insight into mechanisms underlying their formation. Histopathologic studies have shown minimal inflammatory reaction and a predominance of subpial lesions in both MS 5,25,26 and the marmoset experimental autoimmune encephalo myelitis (EAE) model, 27 implying that these mechanisms may differ from lesions in white matter.…”
Section: Discussionmentioning
confidence: 99%
“…4 Other studies show that intracortical lesions exhibit relatively minimal inflammatory reaction. [5][6][7] These studies imply differences in the pathophysiologic processes of gray and white matter lesions that need to be clarified to gain a better understanding of this disease.…”
mentioning
confidence: 99%
“…Grey matter lesions are usually characterised by a relative lack of parenchymal lymphocyte infiltration, deposition of antibody and complement proteins, and blood brain barrier disruption when compared to white matter lesions 12,14,15 . In post mortem samples taken from individuals in the advanced stages of multiple sclerosis, high numbers of immune cells were only detected in Type I grey matter lesions ( Figure 1A): all other grey matter lesions were categorized as relatively "noninflammatory" [11][12][13] .…”
Section: Are White and Grey Matter Damage Linked?mentioning
confidence: 99%